PENERAPAN PROSES ASUHAN GIZI TERSTANDAR TERHADAP ASUPAN ZAT GIZI MAKRO DAN LAMA HARI RAWAT PADA PASIEN GERIATRI DI RUMAH SAKIT - I Kadek Andi Artawa; Ni Komang Wiardani; Pande Putu Sri Sugiani (Jurnal Ilmu Gizi : Journal of Nutrition Science, 2022)
ABSTRACT Geriatric patients are elderly patients with multi-diseases who are prone to malnutrition. One of the efforts to improve macronutrient intake and the length of stay for geriatric patients who are hospitalized in a hospital is the standardized nutrition care process (NCP). Objective: To determine differences in macronutrient intake and length of stay between geriatric patients with standardized NCP and geriatric patients without standardized NCP in the hospital. Method: The type of research that has been done is a quasi-experimental with post test only control group design. The subjects who had fulfilled the inclusion criteria were 36 people then divide into 2 groups, namely the standardized NCP group at RSUD Klungkung and non-standardized NCP group at RSUD Bangli. Data collection on macronutrient intake was carried out by the food weighing method, and data on length of stay was collected by medical record observation. Hypothesis testing is done by unpaired t-test and Mann-Whitney. Results: The average age of the study subjects was 70,08 years and most were in 61-69 years. Assessment of nutritional status based on MNA was obtained at 44,4% of the subjects were malnourished. The results of the unpaired t-test produced a p-value of 0,001 (p0,05) which showed that the average macronutrient intake in the standardized NCP group was significantly higher than the non-standardized NCP group. The average length of stay in the standardized NCP group (7,33 days) was shorter when compared to the non-standardized NCP (10 days). Mann-Whitney’s test produced a p-value of 0,023 (p0,05) showed that there were significant differences in the average length of stay of the two groups. Conclusions and Suggestions. The application of standardized NCP has an effect on improving macronutrient intake and length of stay in geriatric patients, so nutritionists are advised to apply the standardized NCP to geriatric patients to improve their nutritional status. Keyword: the standardized nutrition care process, macronutrient intake, length of stay